HRM practices, organizational citizenship behaviours, and perceived service quality in golf courses - Husin, S.; Chelladurai, P.; Musa, G. (Human Kinetics, 2012)
Three hundred and twenty five employees of 68 golf courses in Malaysia participated in this study investigating the proposed model wherein selected HRM practices (Support at Work, Training, Reward System, Supervisory Assistance, and Performance Appraisal) were seen as influencing organizational citizenship behavior (OCB) which, in turn, was associated with Perceived Service Quality. The results showed that the measurement model and the structural model fit the data very well. Further, all of the paths specified in the model except the one linking Training to OCB were significant with OCB explaining more than 50% of the variance in Perceived Service Quality. Increased support at work, Reward System, Supervisory Assistance, and Performance Appraisal resulted in higher levels of Perceived Service Quality.